Creating a Brand by Innovative Communication Tools - Buadit, Kesinee; Pimproa, Kalaya (NEU ACADEMIC AND RESEARCH JOURNAL, 2021)
Among the rapid changes of globalization era, technologies have been moved forward by communication processes. One of the communication processes aimed at transferring information directly to the consumers. Through the innovative communication tools, Marketing Information System (MKIS) and its diversities, such as statistic data, marketing contents, webpage designs, SWOT analysis, and etc. which have been developed and associated to modernize the digital world. For this era, the marketing that provides only product and its data is inadequate for consumers. One thing needs to be concerned is choosing product. There are a number of promoted product pictures posted through the innovative devices and channels as marketing strategy that brand owner needs to be aware of. Creating a brand with customers, this reminds customers on awareness, consideration. There are various ways to market your bands globalized. Nowadays, communication marketing chances, platforms, and innovative communication tools are influenced in the Era 5.0. Besides that, advertisers, marketing men, business men should keep up with advancements of technologies. Moreover, content marketing has been proved that marketing moves continuously, so we should catch up with consumers’ behaviors.